2017
DOI: 10.1007/s10803-017-3086-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Teacher-as-Coach Model: Improving Paraprofessionals Fidelity of Implementation of Discrete Trial Training for Students with Moderate-to-Severe Developmental Disabilities

Abstract: Ensuring educational progress for students with moderate-to-severe developmental disabilities requires exposure to well executed evidence-based practices. This necessitates that the special education workforce, including paraprofessionals, be well-trained. Yet evidence regarding effective training mechanisms for paraprofessionals is limited. A multiple baseline design across five teachers was used to evaluate the impact of online instructional modules and a Practice-Based Coaching (PBC) model with teacher-as-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 19 publications
2
12
0
Order By: Relevance
“…Results showed that two of the three paraprofessionals increased FCT fidelity to 100% following the introduction of the coaching package. This finding aligns with previous research demonstrating the efficacy of coaching packages on paraprofessional behavior in special education classrooms (Mason et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Results showed that two of the three paraprofessionals increased FCT fidelity to 100% following the introduction of the coaching package. This finding aligns with previous research demonstrating the efficacy of coaching packages on paraprofessional behavior in special education classrooms (Mason et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…Although there are many different coaching models, high-quality coaching generally involves joint planning and development of measurable goals, action planning, data collection, and shared data-driven decision making (Snyder et al, 2015). Much of the coaching research has focused on coaching teachers (Stormont et al, 2015) and less is known about preparing teachers to serve in the coach role (Mason et al, 2017). Research has begun to examine the efficacy of coaching models in which special education teachers serve as coaches for paraprofessionals.…”
mentioning
confidence: 99%
“…Of these students, the authors reported that 108 had autism, 69 had intellectual disability, 12 had both autism and intellectual disability, 16 had multiple disabilities, and 28 had developmental disabilities that were not specified. In the remaining three studies, the authors described the paraprofessionals working with students with multiple disabilities (Da Fonte & Capizzi, 2015), autism (McKenney & Bristol, 2015), or developmental disabilities (Mason et al, 2017), but did not report the number of students. Eighteen studies included only elementary students, 3 included only middle school students, 7 included only high school students, and 5 studies included a combination of students from different levels of schooling…”
Section: Resultsmentioning
confidence: 99%
“…Some studies used technology to deliver training outside of an in‐person format. Specifically, training was delivered in an exclusive online format (Walker & Snell, 2017), a hybrid online/in‐person format (Brock & Carter, 2015; Brock et al, 2017; Da Fonte & Capizzi, 2015; Mason et al, 2017), and through teleconference (Fischer, Clark, Bloomfield, Askings, & Erchul, 2019). Other studies delivered part (Asmus et al, 2017; Brock & Carter, 2015; Carter et al, 2016) or all (Foreman et al, 2014; Heinrich, Collins, Knight, & Spriggs, 2016) of the training in a group in‐person format.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation